I primi borsisti a Roma della nuova Università di Cluj: George Mateescu e Emil Panaitescu - TURCUȘ, Șerban (Studia Universitatis Babeș-Bolyai Historia, 2019)
The first scholarship holders of the new University of Cluj, at the Romanian School in Rome: George Mateescu and Emil Panaitescu. One of the priorities of Cluj University after its inauguration in the autumn of 1919 was the endowment with teachers and their specialization. If some of the teachers were from Transylvania, another part came from the kingdom of Romania in order to help create university specialities in Cluj. Vasile Pârvan was the most important teacher who came to Cluj, but he also brought with him his collaborators from the University of Bucharest. For the study of ancient history, he brought George Mateescu and Emil Panaitescu. Immediately after the inauguration of the courses at the University of Cluj, Pârvan founded in Rome a highly specialized school, the Romanian School in Rome, whose director became. Among the first members of the School he also brought to Rome his two disciples from Cluj, which he specialized in techniques and research methodologies in the history of Antiquity. The two scholars, Mateescu and Panaitescu, will become directors of the Romanian School in Rome after the death of Pârvan and will coordinate new and new specialists from Cluj, Bucharest, Iaşi and Cernăuţi, the institution in Rome becoming the main provider of humanist intellectuals for the Romania of the following decades. Rezumat: Primii bursieri la Roma ai noii Universități din Cluj: George Mateescu și Emil Panaitescu. Una dintre prioritățile Universității din Cluj după inaugurarea sa, în toamna anului 1919, a fost dotarea cu profesori de rang universitar și specializarea acestora în străinătate. Dacă unii dintre profesori erau din Transilvania, o altă parte venea din regatul României pentru a ajuta la crearea de specialități universitare inexistente la Cluj până atunci. Vasile Pârvan a fost cel mai important profesor care a venit la Cluj, dar și-a adus cu el și colaboratorii săi de la Universitatea din București. Pentru studiul istoriei antice i-a adus pe George Mateescu și Emil Panaitescu. Imediat după inaugurarea cursurilor la Universitatea din Cluj, Pârvan a fondat la Roma o școală înalt specializată, Școala Română din Roma, al cărei director a devenit. Printre primii membri ai Școlii i-a adus și la Roma pe cei doi discipoli ai săi din Cluj, pe care i-a pus să se instruiască în tehnici și metodologii de cercetare specifice istoriei antice. Cei doi savanți, Mateescu și Panaitescu, vor deveni directorii Școlii Române din Roma după moartea lui Pârvan și vor coordona în specialitate noi și noi specialiști din Cluj, București, Iași și Cernăuți. Instituția din Roma va deveni principalul furnizor de intelectuali umaniști pentru România în următoarele decenii. Cuvinte cheie: Universitate, Transilvania, Cluj, Școala Română din Roma, Vasile Pârvan.